Valuing brands under royalty relief methodology according to international accounting and valuation standards - Gracia Rubio; Conrado M. Manuel; Francisco Pérez-Hernández (European Journal of Management and Business Economics (EJM&BE), 2016)
The aim of this paper is to introduce a statistical procedure to value a brand by means of which firms may be able to determine the level of implicit royalty that they would charge for the use of their brand, applying multivariate techniques from market references. The study has been based on a statistical contrast of the royalties paid in Spanish franchises belonging to three different industries: food, health and beauty and fashion. Each industry has been segmented using cluster techniques, and then, through linear discriminating analysis, a model is proposed to explain the royalty paid according to certain economic figures of the companies. The implicit impartiality in the development of the model means that it could be generally accepted by analysts, consultants and companies who need to determine the value of a brand.
Keywords: G3; G30; 650; Brand valuation; Business combination; Cluster; Discriminating analysis; Fair value; Intangible asset; Value driver